Hubungan Antara Motivasi Kerja dan Lingkungan Kerja Dengan Kinerja Karyawan Pada Bank BRI Syariah KCP Kebumen - Muhajir, Muhajir; Khasanah, Fitrohtul; Fatonah, Nelli (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
Work motivation is an encouragement to increase the individual efforts of employees in doing their work in order to achieve organizational goals. With the motivation of work makes employees more passionate in carrying out their work. The higher the motivation given, the higher the performance of employees in a company. This study aims to find out how strong the relationship between work motivation and work environment and employee performance at Bank BRI Syariah KCP Kebumen. The sample in this study amounted to 24 people taken from the total number of employee population at Bank BRI Syariah KCP Kebumen. This study used primary data by distributing questionnaires sourced from employees at Bank BRI Syariah KCP Kebumen. Secondary data sourced from documents. Data analysis techniques in this study used multiple creation analysis processed using IMB SPSS Statistic 25. From the results of data processing analysis shows that there is a positive and direct relationship between work motivation and work environment with employee performance, but the closeness of relationships in this study is low at 0.288. Looking at the guidelines for relationship density, this study was in the number 0.20 – 0.399. This means that if the work motivation and work environment improves, the performance of employees at Bank BRI Syariah KCP Kebumen increases.